Factors affecting the cost of production of milk and milk products of crossbred cows (Indian Journal of Animal Production and Management, 2018)
The experiment was carried out with10 Jersey crossbred and 10 Holstein-Friesian crossbred cows during  each of the four seasons viz. Pre-monsoon, Monsoon, Post-monsoon and Winter during the year 2016- 17 to study the effect of feeding practice, genetic group and season on the cost of production of milk and  milk products such as paneer and curd (dahi) of crossbred lactating cows reared under organized farm  condition. The overall mean cost of production of milk, paneer and and curd (dahi) was ₹ 31.73±0.55,  266.47±2.89 and 84.17±0.75 per kg, respectively. There was highly significant difference (p
Keywords: Cost; Crossbred; Dahi; Milk production; Paneer; Season; TMR feeding